2014
DOI: 10.4028/www.scientific.net/amm.556-562.339
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of GNP/Nylon Composites

Abstract: Graphene nanoplatelets (GNP) and nylon (PA) have been often used as thermal filler and matrix and respectively to produce composites. In this work, PA6/PA66/GNP thermal composites were prepared via a melt blending method. Mechanical properties, morphology, and thermal properties of PA6/PA66/GNP composites were investigated. Because the GNP is very expensive, we investigated to use Al2O3 and graphite and examined the characteristics of the prepared composites. Thermal conductivity values of PA6/PA66/GNP composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The flame-retardant properties of PA6 were significantly improved. Xu et al 46 developed PA6/PA66/GNP thermal composites by melt-blending method. The thermal conductivity of composite containing 50 wt% of GNP was measured as 5.03 W m –1 K –1 at 30°C, indicating an increase of more than 15 times compared with that of the neat PA6.…”
Section: Preparation Techniques For G-pa Nanocompositesmentioning
confidence: 99%
“…The flame-retardant properties of PA6 were significantly improved. Xu et al 46 developed PA6/PA66/GNP thermal composites by melt-blending method. The thermal conductivity of composite containing 50 wt% of GNP was measured as 5.03 W m –1 K –1 at 30°C, indicating an increase of more than 15 times compared with that of the neat PA6.…”
Section: Preparation Techniques For G-pa Nanocompositesmentioning
confidence: 99%
“…Methods such as solvent blending and melt blending can provide uniform dispersion of graphene in PA. Zhang et al 25 prepared graphene/PA6 composites by melt processing and showed the effect of graphene nanofiller on crystalline temperature of PA6 was increased due to heterogeneous nucleation. Xu et al 26 produced PA6/PA66/GNP thermal composites by the melt-blending method with improved thermal properties of composite compared to the neat PA6. Roy et al 27 also improved the thermal stability of PA12/ polyethylenimine (PEI)-RGO composites by the melt-mixing process.…”
Section: Introductionmentioning
confidence: 99%